De/constructing Literacies: Considerations for Engagement - Lemieux, Amélie (Peter Lang, 2020)
De/constructing Literacies: Considerations for Engagement reviews and defines the concept of engagement in literacy studies from different epistemologies. Well-suited for literacy researchers and graduate students, it considers the foundations of arts-based research, cognitive psychology, ethnography, phenomenology, posthumanism, with a final chapter on walking methodologies, to better understand how engagement can be framed and looked at in literacy studies.

Porosité et didactique de la littérature au secondaire : Didactisation d’une oeuvre théâtrale et de son adaptation filmique pour un réinvestissement poétique en classe de français - Lemieux, Amélie (La Lettre de l’AIRDF, 2023)

Pour une lecture émancipatoire : bell hooks - Lemieux, Amélie (Revue des sciences de l'éducation, 2022)

M/EDIA/tions: Assises théoriques relatives aux questions d’équité, de diversité, d’inclusion et d’accessibilité (EDIA) pour l’enseignement de la littérature avec le numérique - Lemieux, Amélie (Revue de recherches en littératie médiatique multimodale, 2021)

Antidualisms in maker literacies research: Technological processes, materialities, mappings - Lemieux, Amélie (Education & Didactique, 2021)

Vers une documentation d'oeuvres littéraires numériques queer - Lescouet, Emmanuelle; Vallières, Amélie; Lemieux, Amélie (BD, Littératie et créations numériques : Quels enjeux pour demain?, 2023)

Sur la notion d’engagement envers la lecture : Constats, angles morts et complexités - Lemieux, Amélie; Berthiaume, R. (Nexus, 2023)

Éclosions in literacy research: Rereading Brandt and Clinton's “Limits of the local” - Ferguson, D.; Lemieux, Amélie (Journal of Literacy Research, 2022)

When in doubt, map it out: Teachers’ digital storytelling researched through documentation - Lemieux, Amélie; Mason, S. (Canadian Journal of Learning and Technology, 2022)

Dis/comforting shelfies: Travelling literacies other-wise in disrupted times. - Scott, F.; Lemieux, Amélie; Johnston, K (Digital Culture & Education, 2022)

À l’aube de la transmédialité : de l’oeuvre antérieure comme péritexte - Lemieux, Amélie (Péritexte et transmédialité, 2023)

Visualizing mapping as pedagogy for literacy futures - Lemieux, Amélie; Smith, A.; McLean, C.; Rowsell, Jennifer (Journal of Curriculum Theorizing, 2020)

Crafting stories and cracking codes in a Canadian elementary school - Lemieux, Amélie; Rowsell, Jennifer (Maker Literacies and Maker Identities in the Digital Age: Learning and Playing through Modes and Media, 2021)

Defining artful literacies : Adolescent affects, belonging and cross-sectorial creativity - Lemieux, Amélie; Beaton, E. (Art Education in Canadian Museums: Practices in Action, 2024)

18e séminaire de recherche en littératie médiatique multimodale | LMM - Brunel, Magali; Boutin, Jean-Francois; Coste, Jimmy; Lalonde, Martin; Lemieux, Amélie; Audet, René (2021)

InstaPoésie : de l’espace de partage littéraire virtuel à la production de textes poétiques en classe du secondaire - Lemieux, Amélie; Barton, G.; Lewkowich, D.; White, B.; Gauthier, M.-C.; Beauchamp, F. (Revue de recherches en littératie médiatique multimodale, 2022)

20e séminaire en LMM ... sortez vos paillettes! | LMM - Boutin, Jean-Francois; Amélie Lemieux; Blanchette, Karine; Lalonde, Martin; Vallières, Amélie; Dumoulin, Pierre-Gabriel; Mahieu, Luc; Gladu, Eve; Martel, Virginie; Lacelle, Nathalie; Audet, René; Lahouste, Corentin; et al. (2022)